PENGARUH SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI PADA KANTOR SEKRETARIAT BAGIAN ADMINISTRASI PEREKONOMIAN KABUPATEN KERINCI - Herlina, Vivi (journal of RESIDU, 2018)
Government employees development as human resources influence to officer performance. Government employees development will cause some changes attitude, habit, knowledge and skill. Government employees development is an effort to improve technical, theoritical, conseptual, and moral that approriate with job needed or position through education dan training. This research used quantitative method by quantify attitude, opinion, and people perception or social symptom by using Liker Scale. While, to get information about the influence of human resources on government employees performance in Economic Administrative field Kabupaten Kerinci by using Spearman Rank and Determination Coefficient. This research show that there were some influence between human resources on government employees performance; it's approved by the significant test that Ha is accepted.